Radiation Field Characterization for Cellular Irradiation: Application for Low Energy Beams - Rafael Guimarães Malanga; Thatiane Alves Pianoschi; Cassiana Viccari; Henrique Trombini; Franciele Faccio Busatto; Dinara Jaqueline Moura; Mirko Salomon Alva-Sánchez (Brazilian Journal of Radiation Sciences)
The interaction of radiation with biological tissues may cause some damage. To quantify it, studying cells in vitro is one methodology for analyzing dose deposition in biological tissues because once exposed to radiation, different methods can quantify the biological damage. However, biological tissue culture exposure forms mostly employ high-energy beams (MeV). Thus, this study aims to characterize the radiation field from X-ray equipment using thermoluminescent dosimeters (TLD), to establish an in vitro irradiation protocol of breast cancer and glioblastoma cells for low energies. First, the central axis alignment test was performed to ensure the equipment followed the Normativa IN 90. Then the variation of radiation intensity was analyzed for a 5 x 5 cm² field at distances between 30 and 90 cm from the focal point to the detector. Subsequently, TLD immersed in breast cancer and glioblastoma cellular media were irradiated in a 106 kV and 71 mAs beam to evaluate the dose in cellular media. Simulations were performed with the PENELOPE code to compare with experimental results. The result of the central axis alignment showed that the equipment complies with the current Normativa. The dose distributions for the evaluated distances were more homogeneous for the 40 cm distance, with a standard deviation of 1.7% and 0.9% of the distributions obtained with the TLD and simulation, respectively. Thus, the irradiation field for low energy beams was characterized for a 5 x 5 cm² field for 106 kV and 71 mAs beams at a DFS of 40 cm.